Potensi Penggunaan Insulin Topikal untuk Tata Laksana Luka Diabetik Kronis - Lorettha Wijaya; Erwin Jawan (Journal of Medicine and Health, 2022)
Wound healing disturbances that occur in chronic diabetic wounds result in various complications and cause a significant burden. With the increasing prevalence of diabetes mellitus, it is estimated that the numbers of chronic diabetic wounds and their complications will also continue to increase. One of the latest managements using growth factors for chronic diabetic wounds gives satisfactory results, but their use is still limited because of the high costs. This study aims to explore the effectiveness of using topical insulin as a cheaper and effective alternative therapy in chronic diabetic wounds. The method of this study is a literature review sourced from Google Scholar and ProQuest search engine. Eight articles were obtained that are relevant to be discussed in this study. According to studies conducted so far, topical insulin can improve wound healing through the modulation of inflammation and insulin signaling pathways. In conclusion, there is improved wound healing in diabetic chronic wounds patients that were given topical insulin. Therefore topical insulin should be considered as part of chronic diabetic wounds management. Keywords: wound healing; chronic diabetic wounds; growth factors; topical insulin